Investigation of some recycled oils as fluids for polyurea greases. (3rd June 2019) - El-Adly, Refaat A.; El-Naggar, Ashraf Y.; Hussein, Modather F.; Raafat, Bassem M.
Abstract: The aim of this study is to explore the effect of three types of recycled oils on the preparation of three types of Polyurea greases. In this respect, physicochemical and rheological properties of these oils were determined including hydrocarbon type analysis via gas chromatography. The effect of the recycled oils properties as dispersion medium on performance of prepared polyurea greases was investigated. The obtained greases were tested in accordance with the standards of the National Laboratory for Grease Institute (NLGI) and compared with the Egyptian Standard (ES). Furthermore, these tests have been conducted on commercial polyurea grease in order to determine the efficiency of prepared greases. The results of these tests showed that the physicochemical and wear properties of prepared greases are almost conformity with the commercial one. It was concluded that the recycled oils, especially heavy recycled oil, could use a good dispersion medium for the polyurea grease.